TARI TOPENG MALANGAN SEBAGAI ALTERNATIF WISATA BUDAYA DI KOTA MALANG - Melany - (Program Studi Hospitality dan Pariwisata, 2017)
Results of research on Malangan Mask Dance can be used as an alternative cultural tourism in Malang shows that Malangan Mask Dance has the potential high value artwork and attract domestic and foreign tourists. The selection of this topic is based on cultural tourism trends are increasingly showing its movement today. Malang district government through the Department of Industry and Trade also has a fixed program to help the artisans and art figures to continue to develop his artistic products. Even the dance and mask products Malangan occasionally enliven the world market as a high-value artwork. To date, the cultural tourism in the city of Malang still be less desirable because of the lack of information Malangan mask dance performances as well as the boredom that plagued the present generation. Obviously this will lead to extinction in the future. Therefore, this study raised the Mask Dance Malangan as an alternative cultural tourism. With a qualitative descriptive research method, several approaches were developed to analyze the Mask Dance Malangan be a good cultural region. This approach mencapkup Participatory Planning, potential and characteristics of the product, community development, territorial approach and the optimization potential of cultural products. Malangan Mask Dance is a product of the work of art with the potential to be used as a cultural tourism in the city of Malang. KEYWORDS : Tari Topeng Malangan, Cultural Tourism, Malang